The Investigation Of Translation Accuracy Between Human And Google Translate In Translating Folklores - Zebua, Intan; Sipayung, Kammer; Octaviana, Yessy (Innovative: Journal Of Social Science Research, 2024)
Google Translate is an automatic translation service that has become a very popular and useful tool for various cross-language communication purposes. Human translation is also the process of translating text from one language to another using human expertise, language knowledge, and cultural understanding. This research aims to investigate the accuracy between Google Translate and Human Translation. This research uses and applies Nababan's theory (2012) and the research design uses qualitative methods with case study. The data in this research (clause) were taken from Bilingual books with folklore data sources entitled "An Ant and A Grasshopper" and "Singosari Temple". In this study, translations from Google Translate and Human Translations were assessed by 3 raters. The results of this research are : 1. The accuracy of human translation has an average score of 1,5 which is categorized as less accurate. 2. The accuracy of Google Translate has an average score of 1,7 which is categorized less accurate, so the Google Translate translation score is higher compared to human translation scores